2023
DOI: 10.3390/met13061130
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Response Optimization of Additively Manufactured Ti6Al4V Component Using Grey Relational Analysis Coupled with Entropy Weights

Abstract: Due to its near-net-shape manufacturing and ability to treat challenging-to-manufacture materials such as titanium alloys, Additive manufacturing (AM) is growing in popularity. However, due to the poor surface quality of AM components, finishing processes such as machining are required. One of the most difficult aspects of finishing AM components is the fact that even when using the same machining parameters, the surface roughness can vary significantly depending on the orientation of the part. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In the multi-objective optimization process, Grey relational analysis (GRA), the weighted Grey relational analysis (WGRA) technique for order of preference by similarity to ideal solution (TOPSIS), desirability function (DF), entropy weight method (EWM), and many other techniques are applied for optimize the process parameters [11,12]. GRA and TOPSIS are not specific optimization tools, yet they can be used as part of an optimization process to rank and select the most efficient solution based on multiple criteria.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…In the multi-objective optimization process, Grey relational analysis (GRA), the weighted Grey relational analysis (WGRA) technique for order of preference by similarity to ideal solution (TOPSIS), desirability function (DF), entropy weight method (EWM), and many other techniques are applied for optimize the process parameters [11,12]. GRA and TOPSIS are not specific optimization tools, yet they can be used as part of an optimization process to rank and select the most efficient solution based on multiple criteria.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Some studies have shown that the 3D printing layer orientations considerably affect the final visual appearance of the additively manufactured parts. Milling of the Ti6Al4V [38] and γ-TiAl EBM [33] components and turning of the Ti6Al4V EBM [39] components are examples where the effects of layer orientations have been studied and published. It has been found through investigations that the same machining parameters can produce varying degrees of surface roughness depending on the orientation of the EBM component being machined [40].…”
Section: Introductionmentioning
confidence: 99%